2015
DOI: 10.1186/s13731-015-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Black and Scholes approach: a first systematic literature review

Abstract: Purpose: The aim of the paper is to investigate the Black and Scholes model by providing an updated framework of the international literature on the topic, within the field of real option. The purpose of the research is to identify the relevant literature between 1999 and 2015, together with the most important perspectives on the Black and Scholes model as analysed by scholars, in order to provide a useful support to the academic community in their studies. The investigation was carried out only for its econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Since then the Black–Scholes model has continued gaining popularity in different domains from business (Corrado & Su, 1996) to construction projects (Barton & Lawryshyn, 2011). Del Giudice, Evangelista, and Palmaccio (2016) in his study attempted to review the practicality of Black–Scholes model in different sectors and his outcome revealed that practical application of Black–Scholes model lies in the business studies sector focusing on the financial markets. A study conducted by Hong (2004) used the data from 1994 to 2003 from Malaysian stock markets and concluded that the BSOPM prices were significantly different and were below the market prices.…”
Section: Discussionmentioning
confidence: 99%
“…Since then the Black–Scholes model has continued gaining popularity in different domains from business (Corrado & Su, 1996) to construction projects (Barton & Lawryshyn, 2011). Del Giudice, Evangelista, and Palmaccio (2016) in his study attempted to review the practicality of Black–Scholes model in different sectors and his outcome revealed that practical application of Black–Scholes model lies in the business studies sector focusing on the financial markets. A study conducted by Hong (2004) used the data from 1994 to 2003 from Malaysian stock markets and concluded that the BSOPM prices were significantly different and were below the market prices.…”
Section: Discussionmentioning
confidence: 99%
“…The first review article on option pricing was published by Smith (1976) who tried to provide detailed description and terminologies of different option pricing models. Giudice et al (2015) tried to evaluate existing literature on BSOPM using articles published between 1999 and 2015. This study adopted the systematic literature review technique to analyze the literature and suggested some directions for future research.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Created in 1973 by economists Fischer Black and Myron Scholes, the Black-Scholes model (BSM) became the most used methodology for assessing options and it fostered the development of the derivatives market (Del Giudice et al, 2015;Morreale et al, 2017;Bacelar et al, 2018). The idea behind BSM was a portfolio composed of two assets: the first was called the underlying asset, and the other was a risk-free asset.…”
Section: Real Options Theorymentioning
confidence: 99%